Implementation and Assessment of a Curriculum for Renal Point of Care Ultrasound (POCUS) Training - Yoshiko Ishisaka; Hong Yu Wang; Hayato Mitaka; Elliot Charen; Paru Patrawalla (CINQUILL Medical Publishers Inc., 2024)
Purpose: Renal ultrasound is a non-invasive method to assess for obstructive acute kidney injury (AKI). Point of care ultrasound (POCUS) has been shown to be a good screening tool for obstructive AKI, and with formal training, has high sensitivity and specificity. We aimed to evaluate the effectiveness and feasibility of integrating a novel renal POCUS curriculum into an existing two-week nephrology rotation for internal medicine residents. Methods: We enrolled internal medicine residents rotating on a two-week nephrology rotation between September 2022 and June 2023. Pre-recorded online lectures and a hands-on session on image acquisition were provided. Pre-and post-rotation confidence questionnaires and knowledge tests were collected. At the end of the rotation, participants were evaluated using a skills checklist. Evaluation for knowledge retention was assessed 6-12-months post-rotation with a post-survey and knowledge test. Results: Of the 16 residents that were enrolled, 12 residents completed pre- and post-rotation questionnaires and tests, and 15 residents completed the 6-12-month follow-up. The confidence level showed significant improvement post-test and at 6-12-month follow-up. Knowledge test scores showed a trend towards improvement that did not achieve statistical significance (pre- 6.0 [5.0-7.25], post- 6.5 [5.75-8.0], 6-12-months 7.0 [6.0-8.0] p=0.40). On the skills checklist, an average of 16.8 out of 18 steps were done correctly. Conclusion: Our study showed confidence improvement and a trend towards knowledge improvement after integrating a novel Renal POCUS curriculum into a nephrology rotation. Further iterative changes, such as deliberate practice, or practice with immediate feedback, should be considered.